Trading in Islam: Shariah rules and contemporary applications in Islamic financial transactions / Syed Faiq Najeeb - Najeeb, Syed Faiq (Universiti Teknologi MARA Selangor, 2014)
This paper attempts to comprehensively highlight the various Islamic laws and guidelines which govern contracts of exchange involving selling of goods and trading of debts. Muslim jurists have extensively researched, reasoned and deliberated over centuries in order to compile a comprehensive framework of principles Muslims are required to adhere to when engaging in selling of goods and trading of debts